Behavior of two eco-compatible duplex systems used in the construction industry against corrosion - Seré, Pablo Ricardo (2014)
Two types of coated steels are currently competing in the construction industry: the hot-dip galvanized steel (HDGS) and the 55%Al–Zn alloy coated steel (HDZAS). Both systems are typically coated by a chromate-based conversion film, which is dangerous for human health and environment. Furthermore, for aesthetics purposes and/or to prolong their expected or planned service life, they are painted designing each paint system as a function of the service conditions to which they will be subject to. The present work reports on a comparative study of two duplex systems: steel/metal coating/organic coating. In both cases, the chromate-based pretreatment was replaced by another one that features γ- mercaptopropyltrimethoxysilane (MTMO) as an active element. The organic coating used was a waterbased polyurethane. Behavior of this paint against corrosion was assessed by exposing the samples in salt spray or humidity chambers, and monitoring its evolution by electrochemical impedance spectroscopy, visual observation, scanning electron microscopy and energy dispersive X-ray analysis. The results revealed that: MTMO was suitable for promoting adhesion both in HDGS and HDZAS; in humidity chamber, both duplex systems provided good protection; the presence of corrosion products of the base steel and paint blistering was detected in the HDGS/paint system seventy-two days after exposure; however, 150 days after that, none of these effects were observed in the HDZAS/paint system; differences in behavior were significant in Salt spray chamber: speed of paint delamination from the mark done and the bulk of corrosion products generated was much higher in HDGS/paint system than in HDZAS/paint.